Gambaran Epidemiologi Kasus Tuberkulosis di Kabupaten Sidoarjo Tahun 2019-2021 - Prima Kartika; Eny Qurniyawati (Universitas Airlangga, 2023)
Background: Tuberculosis is an infectious disease that is still a health problem with the highest number of deaths in the infectious disease group which ranks second after Covid-19. Sidoarjo Regency with its tuberculosis cases, always ranks third for the most contributors to issues in East Java during 2019-2021. Objectives: This study aims to provide an overview of tuberculosis cases in Sidoarjo Recency from 2019 to 2021 based on epidemiological approach (person, place, and time). Methods: A descriptive study was conducted by time series in certain time intervals. This study provided an overview of Tuberculosis cases in Sidoarjo Regency in 2019-2021 based on Sidoarjo Regency health profiles and other supporting data that has been published by the related institution. The variables studied included gender, place based on sub-district area, population density, and time. Results: The result showed that the number of tuberculosis cases in Sidoarjo Regency during 2019-2021 has increased, except in 2021. Reports of the number of cases have decreased in line with several studies that show the influence of the Covid-19 pandemic that occurred in early 2020. Cases reported are predominantly male, which is influenced by factors such as differences in lifestyle and behavior. The high number of human immunodeficiency virus cases in Sidoarjo increased susceptibility to tuberculosis infection due to a weaker immune system condition compared to people with good health. Based on the density of the local area, Waru and Taman sub-districts are the most densely populated areas with the most tuberculosis cases compared to other sub-districts in Sidoarjo Regency. Conclusion: The overview of tuberculosis cases in Sidoarjo Regency during 2019-2021 experienced an up-and-down trend. Some of the reasons that support this incident include gender differences, different conditions of vulnerability, location, population density, influence of health services, and the conditions of the Covid-19 pandemic.